2022
DOI: 10.1016/j.heliyon.2021.e08687
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of codon usage in sesame (Sesamum indicum L.)

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 86 publications
(153 reference statements)
1
7
0
Order By: Relevance
“…Plots with slopes close to zero indicate the absence of neutrality, and that selection pressure might be a strong force in shaping codon composition, i.e. selective constraints ( Andargie and Congyi 2022 ; Bahiri-Elitzur and Tuller 2021 ; Muthabathula et al . 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Plots with slopes close to zero indicate the absence of neutrality, and that selection pressure might be a strong force in shaping codon composition, i.e. selective constraints ( Andargie and Congyi 2022 ; Bahiri-Elitzur and Tuller 2021 ; Muthabathula et al . 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…PR2 analysis revealed that TdEXPs and TtEXPs were greatly influenced by the C frequency in the 3rd codon of amino acids. The codon adaptation index (CAI, 0–1.0) was used to estimate the adaptation of genes to codon usage of highly expressed genes [ 52 , 53 ]. Higher CAI values represent a potentially higher level of expression and potentially greater codon usage bias [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have reported mixed results on the effects of gene length on codon bias. This correlation is strongly positive for E. coli genes; strongly negative for D. melanogaster and S. cerevisiae genes ( Moriyama and Powell, 1998 ), Caenorhabditis elegans , and Arabidopsis thaliana ( Duret and Mouchiroud, 1999 ); and weak for sesame ( Andargie and Congyi, 2022 ). Codon bias was significantly positively correlated ( p < 0.001) with gene length in both up-regulated and down-regulated gene sets, indicating that with an increase in length, bias also increased.…”
Section: Discussionmentioning
confidence: 99%